OPTIMALISASI LAHAN PEKARANGAN UNTUK MENDUKUNG KETAHANAN PANGAN DAN EKONOMI KELUARGA - triana, neni; Fauzan; Miswar (Jurnal Gramaswara: Jurnal Pengabdian kepada Masyarakat, 2023)
Food security will remain a major problem in most countries in the world along with increasing population, increasing purchasing power and global climate dynamics. One of the efforts to build food security and the family economy can be done by utilizing available resources, including through the use of yards. This service aims to examine strategies, potential, policies and programs, as well as constraints on the use of the yard to support food security and the economy, especially at the household level. Yard land has the potential to provide family food, reduce household expenses for buying food and increase household income. Several obstacles related to socio-cultural and economic problems are still encountered in the yard use program, including not yet cultivating backyard gardens on an incentive basis, still being part-time and not yet market oriented, not yet having special yard cultivation technology available, and inadequate mentoring processes. Therefore careful planning and cross-sectoral support is needed in the utilization of the yard so that it can be more optimal in supporting food security and the family economy.